The gendarme of Africa : how can France's 2002 military intervention in Cote d' Ivoire be explained? - Moody, Daniel (Department of Political Studies, 2016)
On 19 September 2002, dissatisfied soldiers in Côte d'Ivoire attempted to overthrow Laurent Gbagbo's regime. In response, France rapidly mobilised its military forces, once again intervening in one of its former colonies. This intervention is all the more surprising given the recent and important reforms in France's Africa policy; reforms which led to the increased disengagement of the French military in Africa. In light of this conundrum, this thesis seeks to understand why France pursued intervention in Côte d'Ivoire in 2002. Moreover, given these wide ranging reforms, I seek to understand the extent to which France's intervention in 2002, indeed, represents something new, or is simply another manifestation of France's traditional way of doing this in Africa. In answering these research questions, this thesis combines both quantitative analysis and an in-depth case study of French intervention in Côte d'Ivoire. In applying the results from the analysis to the case study, I find that the French intervention in Côte d'Ivoire is largely consistent with, and indeed indicative of, France's historical modus operandi in sub-Saharan Africa. In sum, I show how France has a plethora of important interests in the Côte d'Ivoire, interests which are shaped by its strong historical relationship with Côte d'Ivoire and which strongly influenced French intervention in 2002. Moreover, circumstances surrounding the 2002 failed coup attempt, notably the deteriorating situation in Côte d'Ivoire, the empowerment of Jacques Chirac and even the mistrust between Chirac and Gbagbo created the conditions which further fostered military interventions. These factors, it is shown, are largely consistent with the general trends of French intervention in sub- Saharan Africa, thus indicating that, despite important French reforms leading up to the 2002 intervention, very little has changed regarding French motives for intervention in sub-Saharan Africa. As such, the results from this thesis indicate that when one of France's important former African colonies is perceived to be under threat, France is bound by historical responsibility and a plethora of deep-seeded interests to deploy its military and attempt to remedy the situation.